Os curumins da terra brasílica : a educação da criança no século XVI e a pedagogia jesuítica - Pereira, Erika Carolina (Universidade Federal de São Carlos, 2007)
This presentation is intended to examine the actions of the priests of the Jesus Society with the indigenous children called for them curumins in Brazil s colonial-sixteenth century. In addition to that, the study of the primary sources were analyzed the priests reports, present in the letters, documents that indicate the assumptions and philosophical teaching of the Jesuits, and secondary sources of the national historiography great names, in order to contextualize the scene of Brazil in the period under question. The information from the records of priests themselves contributed to demonstrate that the Jesuits ended by developing a pedagogy related with the convertion of the Indians. Understood as "educational laboratory" , the period showed a prominent Jesuit practice in the development of strategies for the conversion of gentio . These tools contributed to the indigenous catechesis through the participation of curumim as mediator in the process of Catechesis. The child was seen by Indian priests as a shallow tabula , blank paper for whom everything could be taught. Through the curumim, the priests tried to win the adults. Therefore the strategies developed with the Indian children were the teaching of the language, the theater, music and Christians rituals coupled to the mnemonico education. In addition to religious teaching, the instructions of the reading skills, writing and counting were present in the so-called Houses of bê-á-bá or Confrarias of boys. Thus, the work intends to cooperate in filling some gaps in the historiography of Brazilian children.
Keywords: Educação infantil; Criança; Educação jesuítica; Cartas; Brasil colonial; Child; Education jesuitic; Letters; Brazil colony; CIENCIAS HUMANAS::EDUCACAO